Higher-order beliefs in a Sequential Social Dilemma - Evan M. Calford; Anujit Chakraborty (University of California, Department of Economics, 2023)
Do experimental subjects have consistent first and higher-order beliefs about others? How does any inconsistency affect strategic decisions? We introduce a simple four-player sequential social dilemma where actions reveal first and higher-order beliefs. The unique sub-game perfect Nash equilibrium (SPNE) is observed less than 5% of the time, even though our diagnostic treatments show that a majority of our subjects are self-interested, higher-order rational and have accurate first-order beliefs. In our data, strategic play deviates substantially from Nash predictions because first-order and higher-order beliefs are inconsistent for most subjects. We construct and operationalize an epistemic model of belief hierarchies to estimate that less than 10% of subjects have consistent first and higher-order beliefs.
Keywords: C92; D81; D91; 330; Experimental economics; Higher-order beliefs; Social dilemma